Astrocyte Crosstalk in CNS Inflammation - Linnerbauer, Mathias; Wheeler, Michael A; Quintana, Francisco J (Neuron (Cambridge, Mass.), 2020)
Astrocytes control multiple processes in the nervous system in health and disease. It is now clear that specific astrocyte subsets or activation states are associated with specific genomic programs and functions. The advent of novel genomic technologies has enabled rapid progress in the characterization of astrocyte heterogeneity and its control by astrocyte interactions with other cells in the central nervous system (CNS). In this review, we provide an overview of the multifaceted roles of astrocytes in the context of CNS inflammation, highlighting recent discoveries on astrocyte subsets and their regulation. We explore mechanisms of crosstalk between astrocytes and other cells in the CNS in the context of neuroinflammation and neurodegeneration and discuss how these interactions shape pathological outcomes.